Ulama Kekerasan sebagai Intelektual Kekerasan:Studi Kasus Bom Bunuh Diri Keluarga di Surabaya - Dedy Tabrani, Dedy Tabrani (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
This article aims to conceptualize the role of the violent ulama in the 2018 family suicide bombing terror incident in Surabaya which involved children, mothers, and fathers (nuclear family). The author uses a qualitative approach with direct data sources in the form of interviews with the Surabaya bombing terrorist network and library data. This article concludes that violent clerics are organic intellectuals who are the intellectual actors behind the family suicide bombing.